Multi‐Centre Field Trial to Evaluate the Effectiveness of Clodronic Acid for Navicular Syndrome. (September 2014) - Frevel, M.; King, B.; Kolb, D.; Boswell, R.; Shoemaker, R.S.; Janicek, J.; Cole, R.; Poole, M.; Longhofer, S.
Abstract : Reasons for performing study: Clodronic acid (CA) is a bisphosphonate which inhibits bone resorption through inhibition of formation/dissolution of hydroxyapatite crystals and by direct cellular effects on osteoclasts. The study was conducted to assess the short‐ and long‐term effectiveness of CA for the control of lameness associated with navicular syndrome. Objectives: To demonstrate the effectiveness of CA in navicular syndrome. Study design: Randomised, multi‐centre, double‐masked, placebo controlled field trial in client‐owned horses. Methods: Horses with unilateral or bilateral forelimb lameness (AAEP lameness scale grade ≥ 2 ); positive anaesthesia of the distal palmar digital nerve(s); radiographic evidence of navicular syndrome and the absence of other causes of lameness were eligible for enrolment. Horses were randomised to treatment groups in a 3:1 ratio of CA to saline control. Treatment was administered once via intramuscular injection at 1.2 mg/kg bwt (maximum 765 mg CA or 15 ml saline). Efficacy was assessed by comparing lameness grades before and after treatment. Results: 146 horses of various breeds were enrolled at 6 sites in Germany and US. At 8 weeks, horses in the CA group had a significantly higher success rate than horses in the control group (least squares mean 74.72% vs. 3.30%; P = 0.0028). Efficacy was sustained through 180 days in 66% of horses. Adverse events were few and considered to be mild and transient. Conclusions: Clodronic acid was safe and effective in navicular syndrome. Ethical animal research:  Owners gave informed consent for their horses' inclusion in the study.Sources of funding:  Dechra Ltd.Competing interests:  The late Dr Frevel was a consultant to Omnimedic GbR, which has applied for a patent for the use of clodronic acid for navicular syndrome. Dr Poole is employed by Dechra.